2004
DOI: 10.1530/eje.0.1510015
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in radiological and radionuclide imaging and therapy of neuroendocrine tumours

Abstract: Neuroendocrine tumours (NETs) constitute a heterogeneous group of tumours that are able to express cell membrane neuroamine uptake mechanisms and/or specific receptors, such as somatostatin receptors, which can be of great value in the localization and treatment of these tumours. Scintigraphy with 111

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
91
0
22

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 187 publications
(113 citation statements)
references
References 101 publications
(135 reference statements)
0
91
0
22
Order By: Relevance
“…Although these receptors are not restricted only to NETs, scintigraphy with 111 In-labelled octreotide (Octreoscan) has offered a highly sensitive tool which, when used in the relevant clinical setting, identifies and localises the tumour in patients with NETs (Krenning et al 1993, Olsen et al 1995, Kaltsas et al 2004aFig. 4).…”
Section: Octreotide Scintigraphymentioning
confidence: 99%
See 1 more Smart Citation
“…Although these receptors are not restricted only to NETs, scintigraphy with 111 In-labelled octreotide (Octreoscan) has offered a highly sensitive tool which, when used in the relevant clinical setting, identifies and localises the tumour in patients with NETs (Krenning et al 1993, Olsen et al 1995, Kaltsas et al 2004aFig. 4).…”
Section: Octreotide Scintigraphymentioning
confidence: 99%
“…4). The Octreoscan achieves a sensitivity that ranges between 67 and 100%, depending on the tumour type, and can be used for the diagnosis, staging and follow-up of patients with NETs (Krenning et al 1993, Kaltsas et al 2004a; occasionally, false positive results have been reported (Kwekkeboom & Krenning 2002). A number of NETs may still not be identified with this technique, most probably due to their small tumour size or less expression of the relevant SSTR subtypes 2 and 5;…”
Section: Octreotide Scintigraphymentioning
confidence: 99%
“…Localizing the disease and determining the degree to which it has spread is of great importance for the process of choosing the appropriate therapy, which is why the diagnosis of NETs includes various visualization techniques, including echosonography, computerised tomography, magnetic resonance imaging, positron emission tomography, endoscopic ultrasound and different nuclear medicine visualization methods [6,7]. Over 90% of carcinoids and other NETs are characterized by excessive expression of somatostatin receptors, especially the sstr2 subtype, which is the molecular basis of their in vivo localization and the clinical application of somatostatin analogue in the treatment of these tumors.…”
Section: Introductionmentioning
confidence: 99%
“…The sensitivity of this method increases for detecting hepatic metastases, where it amounts to 50-80%. For larger tumours, mostly non-secreting pancreatic tumours and late-diagnosed glucagonoma, the sensitivity of transabdominal USG is higher [6,[76][77][78].…”
Section: Transabdominal Ultrasonographymentioning
confidence: 99%
“…Neuroendocrine tumours, particularly those with a high connective tissue content, cause limitation of the diffusion of water molecules, which generates intense signals in the DWI sequence, accompanied by lowered ADC. DWI is particularly valuable in tumours with a significant connective tissue component, which are poorly or atypically enhanced after intravenous administration of the contrast agent [6,76,105].…”
Section: Magnetic Resonance (Mri)mentioning
confidence: 99%